2018
DOI: 10.1038/sdata.2018.105
|View full text |Cite
|
Sign up to set email alerts
|

Individual Brain Charting, a high-resolution fMRI dataset for cognitive mapping

Abstract: Functional Magnetic Resonance Imaging (fMRI) has furthered brain mapping on perceptual, motor, as well as higher-level cognitive functions. However, to date, no data collection has systematically addressed the functional mapping of cognitive mechanisms at a fine spatial scale. The Individual Brain Charting (IBC) project stands for a high-resolution multi-task fMRI dataset that intends to provide the objective basis toward a comprehensive functional atlas of the human brain. The data refer to a cohort of 12 par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 129 publications
(83 citation statements)
references
References 57 publications
1
82
0
Order By: Relevance
“…Furthermore, a fundamental limitation of meta-analysis is the spatial blurring that is inherent to combining participants from studies across different labs and coordinate systems. Therefore, extensive recordings of activation recording (that is, deep phenotyping) in a small number of participants 40 and extensive aggregation of activation studies are highly complementary.…”
Section: Different Types Of Parcellation Based On Local Propertiesmentioning
confidence: 99%
“…Furthermore, a fundamental limitation of meta-analysis is the spatial blurring that is inherent to combining participants from studies across different labs and coordinate systems. Therefore, extensive recordings of activation recording (that is, deep phenotyping) in a small number of participants 40 and extensive aggregation of activation studies are highly complementary.…”
Section: Different Types Of Parcellation Based On Local Propertiesmentioning
confidence: 99%
“…As an example, consider again the contrast from the RSVP language task [Pinho et al, 2018, Humphries et al, 2006 in the Individual Brain Charting (IBC) dataset, shown in Fig. 2.…”
Section: Illustration: Using Neuroquery For Post-hoc Interpretationmentioning
confidence: 99%
“…Indeed, we lack the tools to parse the text in articles and reliably identify those that relate to equivalent or very similar contrasts. As an example, consider a study of the neural support of translating orthography to phonology, probed with visual stimuli by Pinho et al [2018]. The results of this study build upon an experimental contrast labeled by the authors as "Read pseudo-words vs. consonant strings", shown in Fig.…”
mentioning
confidence: 97%
“…These data are part of a large-scale mapping project on a limited number of participants, called Human Brain Charting. Data acquisition procedures and initial experiments run in this project are described in (Pinho et al, 2018). In order to link extracted deep video features to the internal representation of videos in each subject we use a simple linear model to fit their brain activity in each voxel.…”
Section: Feature Extractionmentioning
confidence: 99%